A Study on the Development of Soft Skills Among Hospitality Students at Vocational High School - Lore, Rio Setyayudha; Zakariah, Siti Hajar; Tukiran, Nor Anis Intan Aqiah (Journal of Technical Education and Training, 2025)
Many Vocational High School graduates have difficulty getting jobs or developing their careers due to the lack of soft skills needed in the tourism industry. Soft skills such as communication, critical thinking in solving problems, and teamwork are essential in the current job market in Indonesia. This study aims to measure the level of soft skills among hospitality students at Vocational High Schools in Lombok Tengah, Indonesia. This study uses a quantitative approach, with a survey design using a questionnaire that was distributed to 265 hospitality students from seven Vocational High Schools in Lombok Tengah. The questionnaire will assess the level of student soft skills based on student perceptions. The findings found that the level of communication skills, critical thinking in problem-solving skills, and teamwork skills of students is at moderate level (3.62-3.65). In addition, there is no significant difference in soft skills between courses offered among hospitality students which p-value of 0.34. This research is expected to provide knowledge about the importance of mastering soft skills among hospitality students at vocational high schools in Lombok Tengah and assist schools in better preparing graduates to enter the tourism workplace, increasing their chances of getting a job relevant to their field of study.